Toward More Resilient Urban Stormwater Management Systems—Bridging the Gap From Theory to Implementation - van Duin, Bert; Zhu, David Z.; Zhang, Wenming; Muir, Robert J.; Johnston, Chris; Kipkie, Craig; Rivard, Gilles (Frontiers in Water, 2021)
Many publications include references to reliability, risk and resilience, specifically within the context of climate change and rapid urbanization. However, there is a considerable gap between theory and actual implementation by drainage professionals. As such, most drainage professionals will not have an appreciation of a drainage system’s response to events in excess of its original design event. This gap is compounded by the desire towards evaluating components such as “critical infrastructure” for events significantly more severe than ever contemplated. This paper, reflecting the combined wisdom and thoughts of various drainage professionals across Canada involved with the creation of the Canadian drainage standards (CSA W204 and W210), provides a treatise of risk and resilience based on the application of the dual drainage principle. It provides a discussion of key factors including climate change; densification; shape, intensity, duration and spatial extent of storm events, as a function of the normalized capacity or drain down / emptying time of the various components of the drainage system. Commentaries are offered, highlighting the role of appropriate setbacks and freeboard, and focusing on those aspects that have historically been ignored. Avenues to increase system resilience are presented including an evolution in passive and active flow controls, the potential beneficial role of natural systems and low impact development practices as a function of system sensitivity, discussing how options may vary across Canada.